2010
DOI: 10.1111/j.1556-4029.2010.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Analysis of Rough Diamond by LA‐ICP‐MS: A Case of Source Discrimination?*,†

Abstract: Current profiling of rough diamond source is performed using different physical and/or morphological techniques that require strong knowledge and experience in the field. More recently, chemical impurities have been used to discriminate diamond source and with the advance of laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) empirical profiling of rough diamonds is possible to some extent. In this study, we present a LA-ICP-MS methodology that we developed for analyzing ultra-trace element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Published applications include successful attempts to fingerprint so-called 'conflict diamonds' [150,151], columbite-tantalite and other sought-after ores (e.g., [152,153]). Potential can also be recognised in areas such as uranium concentrates.…”
Section: Element Deportment Geometallurgy and Forensic Applicationsmentioning
confidence: 99%
“…Published applications include successful attempts to fingerprint so-called 'conflict diamonds' [150,151], columbite-tantalite and other sought-after ores (e.g., [152,153]). Potential can also be recognised in areas such as uranium concentrates.…”
Section: Element Deportment Geometallurgy and Forensic Applicationsmentioning
confidence: 99%
“…The first paper providing statistically robust forensic data for diamond discrimination by Dalpé et al [45] concluded that much more work is needed to validate the results, which were positive in general. However, all these studies focused on kimberlitic diamonds and avoided alluvial diamonds.…”
Section: Diamondsmentioning
confidence: 99%
“…Discriminant projection analysis is another multivariate statistical technique that aims to classify a high-dimensional dataset into predefined groups known a priori by calculating a linear discriminant function that maximizes ratios between the groups (Izenman, 2008). This method has been used for geological or forensic investigations of trace element or isotopic analyses of minerals (e.g., Dalpé et al, 2010). We have applied DPA to the same element dataset for San Rafael tourmaline (n = 258 spot analyses, 18 variables) as done for PCA, and defined three groups corresponding to the three generations of tourmaline (Tur 1 to Tur 3).…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%